MANAGEMENT OF THE PROCESS OF FORMATION OF MOTIVATION FOR INNOVATIVE ACTIVITY AMONG TEACHERS OF ADDITIONAL EDUCATION - Pakhomova I. I. (Psychological and Pedagogical Research – Tula Region, 2021)
the article describes the diagnostic material that helps to identify the level of development of the motivation of each teacher of additional education for innovation. The results of the study identify the weak positions and allow us to design further work on the formation of motivation for innovation among teachers of additional education. The concepts of innovative activity of additional education, motivation, pedagogical innovation activity are also revealed.
Keywords: педагог; инновационная деятельность; дополнительное образование; innovative activity; teacher; additional education; диагностическая программа; формирование мотивации; motivation formation; diagnostic program